The Iterative Process of Legitimacy-Building in Hybrid Organizations. Issue 6 (July 2022) - Rosser, Christian; Ilgenstein, Sabrina A.; Sager, Fritz
Hybrid organizations face the fundamental challenge of building legitimacy. To deal with this challenge in administrative theory and practice, we apply an analytical framework following an organizational logic of legitimacy building to an exemplary case of hybridity—the Swiss Institute for Translational and Entrepreneurial Medicine. Our framework application illustrates that pragmatic legitimacy (i.e., establishing instrumental value) must be built before moral legitimacy (i.e., fostering normative evaluation) and cognitive legitimacy (i.e., creating comprehensibility), followed by an iterative process of mutual influence between the legitimacy forms. Originating in the management literature, the framework promises new insights for public administration research on hybrids.